Controlled FCC/on-top binding of H/Pt(111) using surface stress - Shuttleworth, I.G. (Applied surface science, 2016)
[Display omitted] •The preferred binding position of H/Pt(111) changes from on-top to FCC as the surface goes approximately from compressive to tensile strain.•Changes in the binding site preference are determined by both the H sPt s and H sPt d interactions.•FCC-bound H produces a state at energies below those of the Pt d-band. The preferred binding site of H/Pt(111) has been shown to be change from the on-top to FCC as the Pt(111) surface goes approximately from a state of compressive to tensile strain. A chemical analysis of the system has shown that for both FCC and on-top bound cases the H sPt s and H sPt d interactions have a similar importance in determining the preferred binding position. It has been seen that FCC-bound H forms a distinct state below the Pt d-band, whereas the on-top bound H does not.